2016
DOI: 10.1242/jeb.146605
|View full text |Cite
|
Sign up to set email alerts
|

Stellate and pyramidal neurons in goldfish telencephalon respond differently to anoxia and GABA receptor inhibition

Abstract: With oxygen deprivation, the mammalian brain undergoes hyperactivity and neuronal death while this does not occur in the anoxiatolerant goldfish (Carassius auratus). Anoxic survival of the goldfish may rely on neuromodulatory mechanisms to suppress neuronal hyper-excitability. As γ-aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the brain, we decided to investigate its potential role in suppressing the electrical activity of goldfish telencephalic neurons. Utilizing whole-cell patch-clamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…The brain was rapidly removed, placed into agar block and transferred to a Leica VT1000 vibratome slicing chamber. For slice preparation, we used telencephalon as a part of fish brain which is tightly connected to feeding behaviour (Lin et al, 2000), and where GABAR response in C. gibelio was clearly demonstrated (Hossein-Javaheri et al, 2017).…”
Section: Electrophysiologymentioning
confidence: 99%
“…The brain was rapidly removed, placed into agar block and transferred to a Leica VT1000 vibratome slicing chamber. For slice preparation, we used telencephalon as a part of fish brain which is tightly connected to feeding behaviour (Lin et al, 2000), and where GABAR response in C. gibelio was clearly demonstrated (Hossein-Javaheri et al, 2017).…”
Section: Electrophysiologymentioning
confidence: 99%
“…Owing to close relationship between the two species, it is reasonable to assume that goldfish also express both GABA A receptor subtypes. In a previous study, we reported that when exposed to severe hypoxia without any pharmacological manipulations, membrane potential of both stellate and pyramidal neurons shift toward a depolarizing GABA A reversal potential (E GABA ), inducing an inhibitory shunt in pyramidal cells only; this depolarization sufficiently generates action potentials in the inhibitory stellate cells, suppressing the overall electrical activity of the brain (10). In this experiment, we observed that the application of both 100 μM bicuculline (Fig.…”
Section: Pds Observed With Gaba a And Gaba B Receptor Inhibitionmentioning
confidence: 64%
“…While recording the electrical activity of goldfish telencephalic neurons following inhibition of GABA A/B receptors, we noticed unusual action potentials that deviated from the expected patterns: depolarization followed by a hyperpolarization ± afterhyperpolarization (10). Particularly of interest, were apparent seizure-like activities (SLA) and a paroxysmal depolarization shift (PDS) in these neurons.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations